Answer:
Step-by-step explanation:
= 4.629 × 10•10•10•10
The equation is y = -2/3x + 6
Answer:
no solution
Step-by-step explanion
there is no solution since the x's cancel out
Answer:
There is not enough information to answer this question
Step-by-step explanation:
Insert x + 3 instead of x into the equation of the function f(x):
f(x) = 3 - 6x²
f(x + 3) = 3 - 6(x + 3)²
use (a + b)² = a² + 2ab + b²
= 3 - 6(x² + 2(x)(3) + 3²) = 3 - 6(x² + 6x + 9)
use distributive property
= 3 + (-6)(x²) + (-6)(6x) + (-6)(9) = 3 - 6x² - 36x - 54
combine like terms
= -6x² - 36x - 51
<h3>Answer: f(x + 3) = -6x² - 36x - 51</h3>